The Possible Role of the Superior Sagittal Sinus in Regulating Cerebrospinal Fluid Dynamics among Preterm Infants: A Case Report and a Review of the Literature - Andreato, Chiara; Uccella, Sara; Battaglini, Marcella; Pacetti, Mattia; Tortora, Domenico; Ramenghi, Luca A. (Neuropediatrics, 2023)
We report the case of a preterm of 27 weeks of gestation who developed posthemorrhagic ventricular dilatation associated to a complete thrombosis of the superior sagittal sinus, for its peculiar interest in clarifying the physiology of the cerebrospinal fluid (CSF) dynamics. The exact CSF volume that must be removed to improve cerebral hemodynamics and outcomes in infants with posthemorrhagic ventricular dilatation is unknown. According to Volpe's studies, a volume of 10 to 15 mL/kg/die of body weight is commonly chosen. The subject we report needed an excessive CSF drainage (up to 32 mL/kg/d), in presence of a functioning external ventricular drain. We review the literature on the topic, and we postulate that the superior sagittal sinus may play an active role in the CSF dynamics of the immature brain (as it happens for the adult brain).
Keywords: prematurity; hydrocephalus; superior sagittal sinus; cerebral venous sinus thrombosis; cerebrospinal fluid dynamics